Socio-cultural, psychological and family aspects of drug addiction of adolescents and its impact: An analysis from Bangladesh perspective - MD. MANJUR HOSSAIN PATOARI (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: In modern times, drug addiction is a widespread social disease that affects every society in the world. The primary purpose of this research is to investigate the socio-cultural, psychological, and familial aspects of drug addiction and the effects of drug addiction on the health, family life, and social impact of the user. Method: The research in this study is qualitative, with information coming from both primary and secondary sources. The districts of Chattogram and Noakhali in Bangladesh have been surveyed for primary data. A total of 136 drug addicts aged 21-42 were chosen for the study. All respondents were given a pre-designed, structured questionnaire to fill out. The information presented here is secondary data gleaned from a wide range of published sources on a global scale. Findings: According to the study results, approximately 65.45% of the total number of people in Bangladesh addicted to drugs became addicted due to various social and cultural causes. The study also revealed that 25% of people became addicted to drugs due to psychological causes, 8.08% became addicted to drugs due to various family problems, and 1.47% became addicted to drugs due to other matters. The research also shows that drug addiction has a negative impact, both physically and mentally, on the person who uses drugs. Memory is one of the functions that is negatively impacted, along with work capacity. Individuals who are addicted to drugs face an increased risk of death as a result of their condition. Implications/Novel Contribution: Drug addiction prevention has already emerged as a significant obstacle for virtually all countries. The most significant implication that can be drawn from this study is that it will be very helpful in cutting down on drug addiction in Bangladesh. It will raise awareness about the effects of drug addiction among adolescents who are addicted to drugs and the guardians of those adolescents. This study opens up a new channel for academics to contribute the knowledge and experience they have gained throughout their careers to the cause of eradicating drug addiction by adding more research into the effects of drug addiction.